Comparison of Porcine Small Intestinal Submucosa versus Polypropylene in Open Inguinal Hernia Repair: A Systematic Review and Meta-Analysis. - Xin Nie; Dongdong Xiao; Wenyue Wang; Zhicheng Song; Zhi Yang; Yuanwen Chen; Yan Gu (PLoS ONE)
Background A systematic review and meta-analysis was performed in randomized controlled trials (RCTs) to compare porcine small intestinal submucosa (SIS) with polypropylene in open inguinal hernia repair. Method Electronic databases MEDLINE, Embase, and the Cochrane Library were used to compare patient outcomes for the two groups via meta-analysis. Result A total of 3 randomized controlled trials encompassing 200 patients were included in the meta-analysis. There was no significant difference in recurrence (P = 0.16), hematomas (P = 0.06), postoperative pain within 30 days (P = 0.45), or postoperative pain after 1 year (P = 0.12) between the 2 groups. The incidence of discomfort was significantly lower (P = 0.0006) in the SIS group. However, the SIS group experienced a significantly higher incidence of seroma (P = 0.03). Conclusions Compared to polypropylene, using SIS in open inguinal hernia repair is associated with a lower incidence of discomfort and a higher incidence of seroma. However, well-designed larger RCT studies with a longer follow-up period are needed to confirm these findings.